Hubungan Kedisiplinan terhadap Sportivitas dalam Kegiatan Ekstrakurikuler Futsal di Sman 1 Cipatat - Muhamad Tajul Arif Denashofar; Sucipto; Riansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the relationship between discipline and sportsmanship among students participating in the futsal extracurricular program at SMAN 1 Cipatat. The study employed a quantitative approach with a descriptive correlational design to obtain empirical evidence regarding the association between the two variables. The sample consisted of 30 students who actively participated in the futsal extracurricular activity and were selected using purposive sampling based on specific criteria. The research instruments were discipline and sportsmanship questionnaires that had been tested for validity and reliability. The reliability test results showed Cronbach’s Alpha coefficients of 0.893 for the discipline variable and 0.918 for the sportsmanship variable, indicating high internal consistency. Data analysis was conducted using the Shapiro–Wilk normality test to ensure data distribution, followed by a correlation test to examine the relationship between variables. The findings revealed a significant relationship between discipline and sportsmanship, with a correlation coefficient of -0.570 and a significance value of 0.001 (p < 0.05). The coefficient indicates a moderate level of correlation with a negative direction. Therefore, it can be concluded that discipline has a significant relationship with students’ sportsmanship in the futsal extracurricular activity at SMAN 1 Cipatat. Keyword : Extracurricular, Discipline, Sportsmanship